Reducing The Risk Of Corruption Through Declaring Property And Income: International Experience And National Practice - Shakurov Rafik (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The paper discusses how mandatory disclosure of assets and income reduces corruption risk by increasing transparency, enabling scrutiny, and deterring corrupt enrichment. Based on global standards and comparative practice, it determines the best practices such as formats, public availability, verification procedures, connection to asset recovery, and sanctions for non-disclosure. The study then examines national practice, assessing legal design, institutional capacity, and enforcement shortfall. Key findings show that statements succeed when they are followed by independent checks, web-based submission, risk-based screening, and public disclosure, while concealment, weak checks, and politization of outcomes erode results. The article concludes on some practical recommendations for improving declaration systems so that they can better avoid corruption and foster citizen trust.